Ertano Col de la Ottiva e altre uccellande - Frau, Giovanni (Traditiones (Ljubljana), 1999)
The author writes about ottiva, a Friulian toponym for which the author accepts the etymology from Lat. altilia, originally denoting the place where people breed birds. This gradually changed into the place where birds are caught. The term presumably originated around Aquileia and later spread to the area north of Venice. The author also briefly discusses other Friulian terms for bird hunting grounds which appeared simultaneously with the antique expression altilia and occasionally even replace it
Keywords: jezikoslovje; linguistics; Slovene; slovenščina; toponimi; etimologija; etymology